Business model innovation of IT management consulting companies based on SAP ERP technology in Indonesia - Blasius Febrianus Dwi SW; Siska Noviaristanti (International Journal of Accounting and Management Information Systems, 2024)
Purpose: This study aims to examine how IT management consulting companies in Indonesia innovate their business models based on SAP ERP technology to remain competitive and adaptable amidst digital transformation demands. It explores the influence of technology, customer needs, profitability, and infrastructure on the evolution of their business strategies. Research methodology: The study employs a qualitative descriptive approach using purposive and snowball sampling techniques. Data were collected through in-depth interviews and observations with top executives and senior consultants from three leading IT consulting firms: PT. Soltius Indonesia, PT. Sigma Cipta Caraka (Telkom Sigma), and PT. Wilmar Consultancy Services. Business Model Canvas (BMC) and Pivot Theory were used as the analytical frameworks to evaluate business model changes and innovation scores. Results: The findings reveal that the consulting companies have shifted from traditional project-based models to data-driven, cloud-based, and subscription-oriented service models. Four main pivot dimensions resource-driven, offer-driven, customer-driven, and finance-driven underpin this transformation. Strategic innovations include co-creation approaches with clients, preconfigured ERP packages, KPI-based outcome services, and integration of AI, cloud, and analytics. These changes enable the companies to address growing demands for digitalization, efficiency, and insight-based decision-making. Conclusions: Business model innovation enables IT consulting firms in Indonesia to adapt to digital transformation. By shifting to cloud-based, data-driven, and subscription models, they enhance flexibility, efficiency, and client value. Success depends on technology, customer needs, and organizational readiness, positioning these firms as strategic partners in digitalization. Limitations: This study is limited to three case studies and relies on qualitative data, which may not capture the full spectrum of innovation practices across the broader consulting industry. The findings are context-specific and may not be generalizable without further quantitative validation. Contribution: This study offers a strategic reference for IT consultants to adapt their business models through innovation aligned with digital trends.